Closure of a local public hospital in Korea: focusing on the organizational life cycle - Yeo YH; Lee KH; Kim HJ (Dove Medical Press, 2016)
Young Hyun Yeo,1 Keon-Hyung Lee,2 Hye Jeong Kim3 1Department of Public Administration, Sunmoon University, Asan, ChungNam, South Korea; 2Askew School of Public Administration and Policy, Florida State University, Tallahassee, FL, USA; 3Department of Public Administration, Sunmoon University, Asan, ChungNam, South Korea Abstract: Just as living organisms have a creation-maintenance-extinction life cycle, organizations also have a life cycle. Private organizations will not survive if they fail to acquire necessary resources through market competition. Public organizations, however, continue to survive because the government has provided financial support in order to enhance public interest. Only a few public organizations in Korea have closed. With the introduction of new public management since the economic crisis in 1997, however, public organizations have had to compete with private organizations. Public hospitals are not free to open or close their business. They are also controlled by the government in terms of their prices, management, budgets, and operations. As they pursue public interest by fulfilling the government’s order such as providing free or lower-priced care to the vulnerable population, they tend to provide a lower quality of care and suffer a financial burden. Employing a case study analysis, this study attempts to understand the external environment that local public hospitals face. The fundamental problem of local public hospitals in Korea is the value conflict between public interest and profitability. Local public hospitals are required to pursue public interest by assignment of a public mission including building a medical safety net for low-income patients and managing nonprofitable medical facilities and emergent health care situations. At the same time, they are required to pursue profitability by achieving high-quality care through competition and the operation of an independent, self-supporting system according to private business logic. Under such paradoxical situations, a political decision may cause an unexpected result. Keywords: local public hospital closure, publicness, organizational life cycle, South Korea